2019
DOI: 10.2106/jbjs.rvw.18.00168
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Preoperative Antibiotics in Elective Soft-Tissue Procedures in the Hand

Abstract: » The use of preoperative antibiotic prophylaxis is not supported for elective cases of patients undergoing soft-tissue hand procedures that are ≤2 hours in length. » The use of preoperative antibiotic prophylaxis is not supported for patients with diabetes undergoing elective, soft-tissue hand surgical procedures. » There is a paucity of literature evaluating the use of preoperative antibiotic prophylaxis in patients with rheumatoid arthritis, those with cardiac valves, and those taking corticosteroids; becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…Multiple studies have found that diabetes is not associated with increased risk for infection following outpatient hand surgery. 6,10 This is an area for improvement and continued discussion at our institution, and may be relevant at other institutions as well.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Multiple studies have found that diabetes is not associated with increased risk for infection following outpatient hand surgery. 6,10 This is an area for improvement and continued discussion at our institution, and may be relevant at other institutions as well.…”
Section: Discussionmentioning
confidence: 98%
“…5 A 2019 review article concluded that the use of preoperative antibiotic prophylaxis (AP) is not supported for elective cases of patients undergoing soft tissue hand procedures less than 2 hours in length, even in patients with diabetes. 6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent data support foregoing the use of preoperative antibiotics for routine, outpatient, soft-tissue procedures, including carpal tunnel, cubital tunnel, and trigger finger releases. [2][3][4][5][6] Antibiotics are not benign and have complications of their own, even when given as one dose, including allergic reactions, resistance, and Clostridium difficile infections. 7 There is a paucity of data for the need for preoperative antibiotics for hardware-based hand procedures.…”
mentioning
confidence: 99%
“… 10 Although current consensus guidelines recommend against the use of prophylaxis prior to clean, soft-tissue procedures, the perceived advantages of antibiotics have led to their widespread use. 10 , 11 , 12 , 13 , 14 Demonstrated benefits of prophylactic antibiotics have been reported in cases of dog and human bites, elbow arthroplasty, and emergency hand operations. 15 , 16 , 17 , 18 In contrast, evidence against prophylaxis suggests that surgical factors, such as poor sterile techniques and operating room setups, or patient-related factors, such as tobacco use and diabetes mellitus, may play greater roles in infection risk.…”
mentioning
confidence: 99%